IMPROVING THE PROFESSIONAL ABILITY OF NURSES IN NURSING INTERVENTIONS IN HOSPITALS THROUGH EVIDENCE-BASED NURSING PRACTICE WORKSHOP - Adin Mu'afiro; Joko Suwito; Kiaonarni Ongko Waluyo; Sri Hidayati; Supriyanto Supriyanto; Hepta Nur Anugrahini (Frontiers in Community Service and Empowerment, 2023)
The evidence-based approach in Indonesia has not yet developed, including the use of research results in practice. Thus it is necessary to grow the attitude, willingness, awareness, and ability to develop EBNP or transform research results into practice so that nurses can improve the "quality of care" for patients. The purpose of community service activities is to improve the professional ability of nurses at RSUD Dr. Sososdoro Djatikoesoemo Bojonegoro in providing Nursing Care through an Evidence-based Nursing Practice (EBNP) workshop. The workshop took place on May 24-25, 2022, and was attended by 30 nurses from the Inpatient Installation. Nurses' knowledge was measured by an evaluation that use pre-test and post-test methods. The skills evaluation was conducted online on July 23, 2022, by presenting the EBNP project plan to be carried out. Community service participants are nurses at RSUD Dr. R Sosodoro Djatikoesoemo Bojonegoro who has characteristics of most (45%) nurses having an age between 41-50 years and having a working period of 11-20 years (44%), and most (67%) educated in Nurses. The functional positions of the most community service participants are Associate Expert nurses at 37% and there are Main Expert Nurses as much as 4%. The results of the activities through the Workshop showed an increase in the capacity of nurses regarding EBNP who previously had very poor knowledge of 19 people (63.3%) and increased to very good knowledge of 12 people (40.0%). Nurses who initially lacked knowledge increased to 3 people (10.0%) with good knowledge, but there were still 7 people (23.3%) who lacked knowledge. However, not all nurses have participated in the EBNP workshop, so it is necessary to conduct a workshop for the next generation so that all nurses can carry out nursing interventions based on evidence-based.